OPTIMALISASI PENGADILAN PERIKANAN DALAM PENEGAKAN HUKUM TINDAK PIDANA PERIKANAN DI PERAIRAN INDONESIA - Sagita, Afrianto (Jurnal Hukum dan Peradilan, 2017)
Indonesia’s has control over vast seas potential to support the country's economy. However, the potential was not optimal because of fishery crime and the lacking of law enforcement in the field of fisheries. This matter becomes very important and strategic in order to support the fishery development in a controlled manner and in accordance with the principles of sustainable fishery management. However, in practice, law enforcement in fisheries shows weaknesses. It is evident from the very complex problems of criminal offenses fisheries, interagency coordination mechanism problems and the establishment of a fishery court to enforce the law that is not evenly distributed throughout the territory of the district court. In resolving these problems, reforms in law enforcement is the key factor that is focused on the legal and human resources. With this support of fishery law enforcement, it is hoped that fisheries development can be carried out in a sustainable manner.Keywords: fisheries crimes, law enforcement, fishery court